Structure and biosynthesis of fungal alpha-glucans - Grün, Christian Hugo (My University, 2003)
The fungal cell wall is unique among eukaryotes and therefore it forms an ideal target for the development of novel antifungal drugs. Fungal cell morphology and integrity depend on a cell-surrounding wall, which is composed of glycoproteins and polysaccharides. Disrupting enzymes that are involved in cell-wall biosynthesis may lead to inviable cells. For the development of polysaccharide-targeted fungicides, understanding the chemical structure and biosynthesis of cell-wall polysaccharides is essential. In this thesis, the chemical structure of cell-wall alpha-glucan is described. Analysis of alpha-glucan isolated from the model yeast Schizosaccharomyces pombe showed that it consisted of two covalently-linked building blocks. In contrast, the same polysaccharide from an alpha-glucan synthase mutant having aberrant cell morphology consisted of a single building block only. It is suggested that a single enzyme is involved in synthesis and coupling of alpha-glucan building blocks. It is further suggested that alpha-glucan biosynthesis might be initiated by a primer oligosaccharide. alpha-Glucan from S. pombe spore walls was also composed of a single alpha-glucan monomer, indicating that two mechanisms for alpha-glucan biosynthesis may exist. When analyzing alpha-glucans from a number of ascomycetous and basidiomycetous fungi, both dimeric and monomeric alpha-glucan structures were identified, indicating that the two biosynthetic mechanisms may be conserved in evolution.
Keywords: Scheikunde; fungi; fission yeast; cell wall; polysaccharides; carbohydrates; alpha-glucan; cell-wall biosynthesis; NMR; HPSEC